Synthesis and bioassay studies of cationic porphyrins for gene transfection delivery - Kiew, Siaw Fui (2013)
Porphyrins are stable aromatic tetrapyrrolic macromolecules found in many natural products such as hemin, chlorophylls and vitamin B12. Interaction ability of cationic porphyrins with nucleic acid and their fluorescent properties for location identification in cellular domain have promoted their uses as potential gene vectors for gene therapy. In this study, basic cationic porphyrins bearing four positive charges were synthesized. Besides, amphiphilic porphyrins anchored with both hydrophobic and hydrophilic moieties were prepared to facilitate membrane penetration and to give a higher cellular uptake. Polyamidoamine(PAMAM)-porphyrin conjugate was also prepared to produce a complex with higher transfection level but with low toxicity. Adler-Longo condensation method was mainly used to synthesize these cationic porphyrin precursors. All cationic porphyrins were obtained in high yield. All of the compounds were characterized using 1H-NMR, 13C-NMR, ultraviolet (UV) and infrared(IR) spectroscopies.Cytotoxicity and cellular uptake of all cationic compounds were tested on Chinese Hamster Ovary (CHO) cells to evaluate their potential uses as gene carriers. Results revealed that all porphyrins show relatively low toxicity towards the cell even at high concentration(100 μM).The 5,10,15,20-tetrakis(N-methyl-4-pyridyl)porphyrin and two amphiphilic cationic porphyrins of 5-hexyl-10,15,20-tris(N-methyl-4-pyridyl) porphyrin and 5-propyl-10,15,20-tris(N-methyl-4-pyridyl)porphyrin which contain three positive charges on the periphery show the highest cellular uptake. It was also found that the amphiphilic cis-porphyrins of 5,10-dipropyl-15,20-bis(N-methyl-4-pyridyl)porphyrin and 5,10-dihexyl-15,20-bis(N-methyl-4-pyridyl)porphyrin exhibited higher cellular uptake compared to their trans-isomers, 5,15-dipropyl-10,20-bis(N-methyl-4-pyridyl)porphyrin and 5,15-dihexyl-10,20-bis(N-methyl-4- pyridyl)porphyrin.